Interleukin (IL)-17A, F and AF in inflammation: a study in collagen-induced arthritis and rheumatoid arthritis. (24th July 2014) - Sarkar, S; Justa, S; Brucks, M; Endres, J; Fox, D A; Zhou, X; Alnaimat, F; Whitaker, B; Wheeler, J C; Jones, B H; Bommireddy, S R
Summary: Interleukin (IL)-17 plays a critical role in inflammation. Most studies to date have elucidated the inflammatory role of IL-17A, often referred to as IL-17. IL-17F is a member of the IL-17 family bearing 50% homology to IL-17A and can also be present as heterodimer IL-17AF. This study elucidates the distribution and contribution of IL-17A, F and AF in inflammatory arthritis. Neutralizing antibody to IL-17A alone or IL-17F alone or in combination was utilized in the mouse collagen-induced arthritis (CIA) model to elucidate the contribution of each subtype in mediating inflammation. IL-17A, F and AF were all increased during inflammatory arthritis. Neutralization of IL-17A reduced the severity of arthritis, neutralization of IL-17A+IL-17F had the same effect as neutralizing IL-17A, while neutralization of IL-17F had no effect. Moreover, significantly higher levels of IL-17A and IL-17F were detected in peripheral blood mononuclear cells (PBMC) from patients with rheumatoid arthritis (RA) in comparison to patients with osteoarthritis (OA). IL-17A and AF were detected in synovial fluid mononuclear cells (SFMC) in RA and OA, with IL-17A being significantly higher in RA patients. Enriched CD3 + T cells from RA PBMCs produced singnificantly high levels of IL-17A and IL-17AF in comparison to OA peripheral blood CD3 + T cells. IL-17A, F and AF were undetectable in T cells from SFMCs from RA and OA. While IL-17A, F, and AF were all induced during CIA, IL-17A played a dominant role. Furthermore, production of IL-17A, and not IL-17F or IL-17AF, was elevated in PBMCs, SFMCs and enriched peripheral blood CD3 + T in RA.